Chondrosarcoma Arising from the Posterior Iliac Crest Extending into the Spinal Canal. (19th July 2021) - Wada, Kota; Sakamoto, Akio; Kato, Rei; Noguchi, Takashi; Shimizu, Takayoshi; Otsuki, Bungo; Murata, Koichi; Fujibayashi, Shunsuke; Matsuda, Shuichi
Abstract : Chondrosarcoma is a malignant tumor characterized by the production of a cartilage matrix. Extension into the spinal canal from the extracannular space is seen mainly for neurogenic tumors, but it is rare in nonneurogenic tumors. A 75-year-old woman suffered from sciatic pain and numbness in her lower left extremity. The diagnosis was of a low-grade conventional chondrosarcoma, which originated from the posterior ilium with an intraspinal extension at the level of the sacrum, compressing the cauda equina. The tumor extended further into the S1 sacral anterior foramen, in the shape of a dumbbell. The tumor was resected in several blocks posteriorly, and the dumbbell-shaped tumor in the S1 foramen was resected by widening the S1 foramen from behind. The posterior extension of the iliac tumor seemed prevented by the posterior sacroiliac ligament, and the tumor extended into the canal. Here, we report that the iliac chondrosarcoma extending into the spinal canal is rare for this tumor type. An understating of the tumor extension is important for planning the surgical strategy.